Modeling Contractor’s Cash-in-Flow in Public School Building Projects in Karbala - Khaled, Zeyad S. M.; Aswed, Gafel Kareem (Al-Nahrain Journal for Engineering Sciences, 2017)
Public school building projects in Karbala Province experiences payment problems due to improper cash-flow planning by both parties; contractors and clients. These payment problems lead to work stoppages and conflicts. This research aims at developing a suitable model to forecast the expected contractors’ cash-in-flow in public school building projects in Karbala based on historical data. Complete sets of interim payments of (33) out of (38) school building projects finished in the years (2007-2012) in Karbala were interpolated using seven different regression methods namely;  Polynomial, Gompertz, Morgan-Morgan-Finney, Logistic, Exponential, Gaussian and Linear in order to identify the best-suited model. It is found that the third degree polynomial model is more suitable for cash-in-flow forecasting of the case under study with coefficient of correlation of (97.89%) and standard error of (0.0441). Data of the remaining (5) projects were used to test the validity of the best-fitted model using Mean Absolute Percentage Error, Root Mean Square Error and Average Accuracy Percentage. The model is expected to be of high advantage in predicting contractors’ cash-in-flow in public school building projects in Karbala, and consequently clients’ cash-out-flow as well._x000D_